KEKERASAN DALAM NOVEL LAUT BERCERITA KARYA LEILA S. CHUDORI - Anisa Fajriana Oktasari; Alan Farizi (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Violence is a psychological activity in individual life as a result of emotional outbursts and it manifested in actions that can harm others people. The phenomenon of violence that occurs in reality often become a source of inspiration or idea for a writer such as Leila S. Chudori. Through her novel, Laut Bercerita (2017), he describes the violence in the life story experienced by the main character: Biru Laut. The data analysis technique is carried out by (1) identifying the data, namely recording all forms of violence in the novel; (2) classifying data, namely sorting out physical and non-physical violence; (3) interpreting data, namely interpreting each paragraph or sentence according to the researcher's understanding based on theory; and (4) describing the data, namely detailing in depth and focus so that the problem to be answered is found. As a result, in the novel of Laut Bercerita by Leila S. Chudori, there are two types of violence, namely (1) physical violence, in the form of fists, kicks, slaps, etc. and (2) non-physical violence, in the form of fear, sadness, trauma, and other psychological disorders.